Monetary Policy Effectiveness on Inflation and Growth Economy in Century Covid-19 Pandemic - Anggirini Liritiovani Manullang; Dedy Harianto Hutasoit; Khairani Alawaiyah Matondang; Riza Indiriani (PT FORMOSA CENDEKIA GLOBAL, 2023)
This pandemic has caused many countries to experience difficulties as their economies decline. Bank Indonesia is the governing body for determining monetary policy. This study aims to determine the role of monetary policy set and implemented by Bank Indonesia in dealing with the Covid-19 pandemic in Indonesia. The method in this research is descriptive qualitative research taking a lot of data from the literature and reports released by Bank Indonesia taking and collecting data through libraries research. the results of this study indicate several accommodative macroprudential policies, rupiah exchange rate stability policies, policies for purchasing government securities from the secondary market, policy interest rates reductions (BI7DRR), and policies for distributing social assistance (bansos) with the government. This study concludes that Bank Indonesia is seriously in dealing with economics problems during the Covid-19 pandemic.